F129. Detection and characteristics of temporal encephaloceles in patients with refractory epilepsy. (May 2018) - Campbell, Zeke; Edwards, Jonathan C.; Bonilha, Leonardo; Yazdani, Milad
Abstract : Introduction: Temporal encephaloceles (TEs) have recently garnered interest in patients with prior MRI-negative refractory temporal lobe epilepsy (RTLE) as a potential source of focality. Careful review by an experienced neuroradiologist may yield improved detection of TEs, and other clinical, neurophysiologic, and radiologic findings may predict their presence. Methods: Data were reviewed retrospectively on patients at our institution who were presented at a multidisciplinary conference for refractory epilepsy between January 1, 2010 and December 31, 2016. Clinical, neurophysiologic, and imaging data were collected. An expert neuroradiologist reviewed the latest MRI brain on patients for whom one was available, noting the presence or absence of temporal encephaloceles, as well as other associated imaging characteristics. Results: A total of 434 patients were reviewed, nine of whom were excluded due to lack of an available MRI. Seven patients had TEs reported on initial imaging, while 52 patients (10 with left only, nine with right only, and 33 with bilateral) had a total of 192 TEs (95 on the right and 97 on the left) identified on expert review. Patients with TEs tended to be female (43/52 vs. 205/373), obese (BMI 37.1 ± 10.5 vs. 29.4 ± 8.01 kg/m 2 ), older (43.3 ± 12.1 vs. 36.7 ± 13.5 years), have a later age at onset (33.3 ± 12.3 vs. 16.5 ± 14.3 years) compared to patients without TEs. Ictal scalp EEG was available in 394 patients. Seizure onset among patients without TEs was reported as temporal in 182 (53%), non-localizable in 98 (29%), and non-temporal (i.e. generalized or extra-temporal) in 63 (18%), compared to patients with TEs, whose seizure onset was temporal in 46 (90%), non-localizable in five (10%), and non-temporal in none. Fifty-five patients underwent intracranial monitoring. Intracranial EEG seizure onset in patients without TEs was reported as temporal in 28 (62%), non-localizable in nine (20%), extra-temporal in seven (16%), and independent temporal and extra-temporal in one (2%). Seizure onset on intracranial EEG in patients with TEs was temporal in seven (78%), independent temporal and extra-temporal in one (11%), and no seizures were captured in one patient (11%). Conclusion: Careful review of MRI in patients with refractory epilepsy by a board-certified neuroradiologist can increase the detection of subtle TEs, which may be a source for focal refractory seizures. Certain clinical and neurophysiologic findings should raise the suspicion for the presence of TEs, although further studies are necessary to determine their epileptogenicity and response to individual therapies.